High-performance epoxy molding compound and preparation method thereof
By using the surface of nano -nano -oxide silica particles to cover the oxygen oxygenne as the filler, the internal stress problem formed after the curing of epoxy plastic seals is cured, which significantly improves its heat resistance, flame retardant and mechanical properties. Package of small -volume electronic devices.
Patent Information
- Application Number
- CN202411476984.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-21
AI Technical Summary
The internal stress formed by the shrinkage of existing epoxy plastic sealing materials after curing cannot be well solved, resulting in insufficient stability of the packaging material and cannot meet the packaging requirements of highly integrated and small-volume electronic devices.
Nano-modifiers are used as fillers, and the nano-silica particles coated with graphene oxide on the surface reduce the stacking of the fillers in the matrix resin and achieve uniform dispersion, thereby improving the flame retardancy, high temperature resistance and mechanical properties of the plastic sealant.
The heat resistance, flame retardant performance and mechanical properties of the epoxy plastic encapsulation compound have been significantly improved, and the toughness is high. It is suitable for packaging fields such as chips, memories, and circuit boards, and meets the packaging requirements of highly integrated, small-volume electronic devices.
Smart Images

Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastic packaging materials, and in particular to a high-performance epoxy plastic packaging material and a preparation method thereof. Background Art
[0002] Epoxy moulding compound (EMC) is a one-component thermosetting plastic, the main components of which are epoxy resin, phenolic resin, latent accelerator, silicon powder, stress modifier, wax, carbon black, etc. It is mainly used in the electronic packaging industry. In recent years, plastic packaging technology has developed in the direction of thinness and high density, which requires the cured plastic molding compound to have the characteristics of low expansion coefficient, low dielectric constant, low modulus, low water absorption, high fluidity, etc.
[0003] Epoxy resin is generally a type of high molecular polymer with two epoxy groups in the organic molecule. Its existence form can be divided into viscous flow state and solid state according to molecular weight. After curing, it has good mechanical properties and higher weather resistance than other resins. It is not only widely used in high-end fields such as aerospace and chip packaging, but also occupies an important position in people's daily necessities such as coatings and adhesives. Because of its low price, simple curing molding process and good weather resistance, its synthesis and modification research is becoming more and more important. Since the large-scale application of epoxy resin, its new varieties and corresponding curing agents have emerged in an endless stream, and the processing technology has been continuously innovated, which has led to its rapid development. Epoxy resin can present different properties when cured with different curing agents. Its curing temperature is divided into three types: low, medium and high, and the curing time can be instantaneous or slow. Therefore, epoxy resin has strong coverage for application occasions. Epoxy resins with excellent performance have small changes in epoxy value, concentrated molecular weight distribution, light color, low impurity content, and low organic chlorine content.
[0004] Since the development of epoxy resin, its types are still being updated. The classification methods include room temperature state and molecular structure. According to the room temperature state, it can be divided into viscous flow state and solid state. According to the molecular structure, it can be divided into glycidyl ether, glycidyl ester, glycidyl amine, linear aliphatic and alicyclic epoxy resins.
[0005] As electronic devices develop towards high integration and small size, the requirements for packaging are getting higher and higher. Epoxy resin materials have good water resistance and heat resistance, but the internal stress caused by its shrinkage has not been well resolved. Therefore, the most important point in the process of modifying it is to improve its toughness. The enhancement of toughness can reduce the internal stress caused by the shrinkage of epoxy resin after curing and reduce the probability of damage to the packaged material.
[0006] Chinese invention patent CN 115558099 B discloses a hyperbranched polyphenylene ether epoxy plastic encapsulation material, the structural formula of which is: , wherein R is a cyano group. The hyperbranched polyphenylene ether epoxy molding material can achieve high dispersibility and improve internal stress and packaging stability, and has a good packaging effect on electronic devices such as LED chips. At the same time, its synthesis method is disclosed, the process is simple, the raw materials are easily available, and it is suitable for large-scale promotion. The material has a high glass transition temperature and a high thermal decomposition temperature, and can be used in packaging fields such as chips, memory devices, and circuit boards. Although the hyperbranched polyphenylene ether epoxy molding material can improve the toughness of the molding material to a certain extent, since it is still not an organic rigid molecule, its mechanical improvement performance still cannot meet the existing needs. Summary of the invention
[0007] The purpose of the present invention is to provide a high-performance epoxy molding compound and a preparation method thereof, which has good heat resistance and flame retardancy, good mechanical properties, high toughness, is significantly superior to existing products, has simple process, strong applicability, and uses easily available raw materials, and can be used in packaging fields such as chips, memory devices, and circuit boards.
[0008] The technical solution of the present invention is achieved in this way: The invention provides a high-performance epoxy molding compound, which is prepared from the following raw materials by weight: 55-60 parts of base resin, 35-40 parts of curing agent, 400-500 parts of filler, 3-4 parts of accelerator, 3-4 parts of flame retardant and 4-6 parts of coupling agent; the filler is a nano modifier, and the nano modifier is wrinkled graphene-coated nano silica with surface modified by polydopamine.
[0009] As a further improvement of the present invention, the matrix resin is an epoxy resin, selected from at least one of o-cresol-formaldehyde epoxy resin, crystalline biphenyl epoxy resin, dicyclohexane pentadiene phenol epoxy resin, biphenyl aralkyl epoxy resin, and biphenyl aralkyl epoxy resin.
[0010] As a further improvement of the present invention, the curing agent is a phenolic resin, which is at least one selected from linear phenol formaldehyde resin, biphenyl aralkyl type phenolic resin, and X-LOCK type phenolic resin.
[0011] As a further improvement of the present invention, the preparation method of the nano modifier is as follows: S1. Dispersing graphene oxide in water, adding nano-silica, stirring and mixing, spray drying, and obtaining wrinkled graphene oxide-coated nano-silica; S2. adding the wrinkled graphene oxide-coated nano-silica to water, adding dopamine hydrochloride and a catalyst, heating and stirring the reaction, centrifuging, washing, and drying to obtain modified wrinkled graphene oxide-coated nano-silica; S3. The prepared modified wrinkled graphene oxide coated nano-silica is reduced with hydrazine hydrate vapor to prepare a nano-modifier.
[0012] As a further improvement of the present invention, the mass ratio of the graphene oxide and the nano-silicon dioxide in step S1 is 3-5:10, and the average particle size of the nano-silicon dioxide is 80-120nm; the mass ratio of the wrinkled graphene oxide-coated nano-silicon dioxide, dopamine hydrochloride and the catalyst in step S2 is 10:4-6:0.5-1, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 40-50°C, and the time is 3-5h; the reduction time in step S3 is 10-12h.
[0013] As a further improvement of the present invention, the promoter is a mixture of benzoquinone and triphenylphosphine complex in a molar ratio of 0.5-1.5:1.
[0014] As a further improvement of the present invention, the flame retardant is selected from at least one of N,N'-diglycidyl-2,4,6-tribromoaniline, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and red phosphorus.
[0015] As a further improvement of the present invention, the coupling agent is a silane coupling agent, selected from at least one of KH550, KH602, KH792, and KH560, preferably, a mixture of KH550 and KH560, with a mass ratio of 3-5:4.
[0016] The present invention further protects a method for preparing the above-mentioned high-performance epoxy molding compound, comprising the following steps: (1) Weigh the raw materials according to the proportion; (2) The raw materials are mixed and added into an open mixer for heating and mixing, cooled and crushed, sieved and pressed to obtain a high-performance epoxy molding compound.
[0017] As a further improvement of the present invention, the heating temperature is 80-90°C, the mixing time is 4-7min, the sieving mesh size is 40-60 mesh, the pressing conditions are 170-180°C, 6-8MPa, mold closing 50-70s, and pressure holding 50-70s.
[0018] The present invention has the following beneficial effects: Adding micron-sized SiO2 filler to the molding compound often causes blockage. However, adding nano-SiO2 filler, due to its large specific surface area and excessively high surface free energy, will easily cause agglomeration, sedimentation, phase separation and other phenomena after being added to the epoxy resin, so that the characteristics of the nano-SiO2 particles in the epoxy molding compound are difficult to be effectively utilized.
[0019] The present invention is based on nano-SiO2 particle filler, the surface of which is coated with graphene oxide. After spray drying, the mixed liquid passes through a nozzle under the action of air pressure and is broken into small droplets, which enter a cyclone separator together with heated nitrogen. During the spray drying process, the solvent evaporates rapidly, resulting in a volume shrinkage of the droplets, which are separated by a cyclone to form wrinkled graphene oxide-coated nano-SiO2 particle filler. The wrinkled structure can effectively reduce the stacking of the filler in the matrix resin, avoid agglomeration caused by a high specific surface area, and achieve uniform dispersion, thereby fully realizing the flame retardant, high temperature resistance and mechanical enhancement properties of the filler. However, the structure in the graphene oxide state has a poor mechanical enhancement effect.
[0020] The surface of the prepared wrinkled graphene oxide-coated nano-silica is coated with a layer of polydopamine by forming hydrogen bonds with polydopamine through hydroxyl groups. The multi-amino structure enables the nano-modifier to react with epoxy groups, so that it can be dispersed in the matrix resin repeatedly and evenly with good compatibility. At the same time, after subsequent reduction, the graphene oxide is converted into graphene, which further improves the mechanical modification effect on the plastic packaging material.
[0021] The high-performance plastic packaging material prepared by the invention has good heat resistance and flame retardancy, good mechanical properties, high toughness, and is significantly superior to existing products. It has simple process, strong applicability, and easy-to-obtain raw materials, and can be used in packaging fields such as chips, memory devices, and circuit boards. DETAILED DESCRIPTION
[0022] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] Graphene oxide is prepared by the improved Hummers method, and the specific method is as follows: Step 1, weigh 10g of natural graphite powder, 4g of potassium persulfate, and 10g of phosphorus pentoxide, add them into a three-necked flask containing 25mL of sulfuric acid while stirring, first react in a constant temperature water bath at 60°C for 3h, then move the three-necked flask into a constant temperature water bath at 25°C for 5h, filter, wash with deionized water to neutrality, and dry in air to obtain pre-oxidized graphite; Step 2: Weigh 1g of pre-oxidized graphite, add it to a three-necked flask with 25mL of sulfuric acid while stirring, put it in an ice-water bath, and after the pre-oxidized graphite is completely dissolved, add 3g of potassium permanganate, react for 2h, then move the three-necked flask to a constant temperature water bath at 35°C to react for 40min, finally add deionized water, continue to react at 35°C for 1h, and finally add 30% H2O2 until no gas is generated and the solution turns bright yellow. Centrifuge and filter while hot, and wash with a large amount of 5% hydrochloric acid and deionized water until neutral. After the precipitate is ultrasonically shaken for 1h, dry it at 90°C for 24h to obtain graphene oxide.
[0024] Preparation Example 1 Preparation of Nano-Modifier Here’s how: S1. 3 g of graphene oxide was dispersed in 500 mL of water, 10 g of nano-silica having an average particle size of 100 nm was added, the mixture was stirred and mixed evenly, and spray-dried to obtain wrinkled graphene oxide-coated nano-silica; S2. 10 g of wrinkled graphene oxide-coated nano-silica was added to 200 mL of water, 4 g of dopamine hydrochloride and 0.5 g of catalyst were added, heated to 40 ° C, stirred for 3 h, centrifuged, washed, and dried to obtain modified wrinkled graphene oxide-coated nano-silica; The catalyst is a Tris-HCl solution with a pH of 8.5; S3. The prepared modified wrinkled graphene oxide-coated nano-silica is subjected to hydrazine hydrate vapor reduction for 10 hours to obtain a nano-modifier.
[0025] Preparation Example 2 Preparation of Nano-Modifier Here’s how: S1. 5 g of graphene oxide was dispersed in 500 mL of water, 10 g of nano-silicon dioxide having an average particle size of 100 nm was added, the mixture was stirred and mixed evenly, and spray dried to obtain wrinkled graphene oxide-coated nano-silicon dioxide; S2. Add 10 g of wrinkled graphene oxide-coated nano-silica to 200 mL of water, add 6 g of dopamine hydrochloride and 1 g of catalyst, heat to 50 ° C, stir and react for 5 h, centrifuge, wash, and dry to obtain modified wrinkled graphene oxide-coated nano-silica; The catalyst is a Tris-HCl solution with a pH of 9.5; S3. The prepared modified wrinkled graphene oxide-coated nano-silica is subjected to hydrazine hydrate vapor reduction for 12 hours to obtain a nano-modifier.
[0026] Preparation Example 3 Preparation of Nano-Modifier Here’s how: S1. 4 g of graphene oxide was dispersed in 500 mL of water, 10 g of nano-silica having an average particle size of 100 nm was added, the mixture was stirred and mixed evenly, and spray dried to obtain wrinkled graphene oxide-coated nano-silica; S2. Add 10 g of wrinkled graphene oxide-coated nano-silica to 200 mL of water, add 5 g of dopamine hydrochloride and 0.7 g of catalyst, heat to 45 ° C, stir and react for 4 h, centrifuge, wash, and dry to obtain modified wrinkled graphene oxide-coated nano-silica; The catalyst is a Tris-HCl solution with a pH of 9; S3. The prepared modified wrinkled graphene oxide-coated nano-silica was subjected to hydrazine hydrate vapor reduction for 11 hours to obtain a nano-modifier.
[0027] Comparative Preparation Example 1 Compared with Preparation Example 3, the difference is that the preparation method is different: 10 g of nano-silicon dioxide with an average particle size of 100 nm was added to 200 mL of water, 5 g of dopamine hydrochloride and 0.7 g of a catalyst were added, heated to 45° C., stirred for reaction for 4 h, centrifuged, washed, and dried to obtain a nano-modifier.
[0028] Comparative Preparation Example 2 Compared with Preparation Example 3, the difference is that step S3 is not performed.
[0029] S1. 4 g of graphene oxide was dispersed in 500 mL of water, 10 g of nano-silica having an average particle size of 100 nm was added, the mixture was stirred and mixed evenly, and spray dried to obtain wrinkled graphene oxide-coated nano-silica; S2. 10 g of wrinkled graphene oxide-coated nano-silica was added to 200 mL of water, 5 g of dopamine hydrochloride and 0.7 g of catalyst were added, heated to 45 ° C, stirred for 4 h, centrifuged, washed, and dried to obtain a nano-modifier; The catalyst is a Tris-HCl solution with a pH of 9. Example 1
[0030] Raw material composition (parts by weight): 55 parts of NC-3000 biphenyl aralkyl epoxy resin (Mitsubishi Chemical Corporation), 35 parts of PF-8011 linear phenol formaldehyde resin (Jinan Shengquan Group Co., Ltd.), 400 parts of the nano-modifier prepared in Preparation Example 1, 3 parts of accelerator, 3 parts of N,N'-diglycidyl-2,4,6-tribromoaniline, and 4 parts of coupling agent. The accelerator is a mixture of p-benzoquinone and triphenylphosphine complex in a molar ratio of 0.5:1. The coupling agent is a mixture of KH550 and KH560 in a mass ratio of 3:4.
[0031] This embodiment provides a method for preparing a high-performance epoxy molding compound, comprising the following steps: (1) Weigh the raw materials according to the proportion; (2) The raw materials were mixed and added to an open mixer and heated to 80°C, mixed for 4 minutes, cooled to room temperature, crushed, passed through a 40-mesh sieve, 170°C, 6MPa, molded for 50 seconds, and maintained at pressure for 50 seconds to obtain a high-performance epoxy molding compound. Example 2
[0032] Raw material composition (parts by weight): 60 parts of SQCN700-2 type o-cresol type epoxy resin (Jinan Shengquan Group Co., Ltd.), 40 parts of MEH-7851 type biphenyl aralkyl type phenolic resin (Meiwa Industry Co., Ltd.), 500 parts of the nano modifier prepared in Preparation Example 2, 4 parts of accelerator, 4 parts of red phosphorus, and 6 parts of coupling agent. The accelerator is a mixture of p-benzoquinone and triphenylphosphine complex in a molar ratio of 1.5:1. The coupling agent is a mixture of KH550 and KH560 in a mass ratio of 5:4.
[0033] This embodiment provides a method for preparing a high-performance epoxy molding compound, comprising the following steps: (1) Weigh the raw materials according to the proportion; (2) The raw materials were mixed and added to an open mixer and heated to 90°C, mixed for 7 minutes, cooled to room temperature, crushed, passed through a 60-mesh sieve, 180°C, 8MPa, molded for 70 seconds, and maintained at pressure for 70 seconds to obtain a high-performance epoxy molding compound. Example 3
[0034] Raw material composition (parts by weight): 58 parts of YX-4000H crystalline biphenyl epoxy resin (Mitsubishi Chemical Corporation), 37 parts of MEH-7800 X-LOCK phenolic resin (Meiwa Sangyo Co., Ltd.), 450 parts of the nano-modifier prepared in Preparation Example 3, 3.4 parts of accelerator, 3.6 parts of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, and 5 parts of coupling agent. The accelerator is a mixture of benzoquinone and triphenylphosphine complex in a molar ratio of 1:1. The coupling agent is a mixture of KH550 and KH560 in a mass ratio of 4:4.
[0035] This embodiment provides a method for preparing a high-performance epoxy molding compound, comprising the following steps: (1) Weigh the raw materials according to the proportion; (2) The raw materials were mixed and added to an open mixer and heated to 85°C, mixed for 5 minutes, cooled to room temperature, crushed, passed through a 50-mesh sieve, 175°C, 7MPa, molded for 60 seconds, and maintained at pressure for 60 seconds to obtain a high-performance epoxy molding compound.
[0036] Comparative Example 1 Compared with Example 3, the difference is that the nano modifier is prepared by Comparative Preparation Example 1.
[0037] Comparative Example 2 Compared with Example 3, the difference is that the nano modifier is prepared by Comparative Preparation Example 2.
[0038] Test Example 1 The high performance epoxy molding compounds prepared in Examples 1-3 of the present invention and Comparative Examples 1-2 were tested for bending strength, bending modulus, and deflection according to the method specified in SJ / T11197-2013. The results are shown in Table 1.
[0039]
[0040] In terms of modulus and deflection, lower modulus and larger deflection will prevent the chip from being damaged due to excessive stress during hot and cold shock tests on the packaged product.
[0041] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A high performance epoxy molding compound, characterized in that: The invention is prepared from the following raw materials in parts by weight: 55-60 parts of base resin, 35-40 parts of curing agent, 400-500 parts of filler, 3-4 parts of accelerator, 3-4 parts of flame retardant and 4-6 parts of coupling agent; the filler is a nano-modifier, and the nano-modifier is wrinkled graphene-coated nano-silica with the surface modified by polydopamine.
2. The high performance epoxy molding compound according to claim 1, characterized in that: The matrix resin is an epoxy resin, which is selected from at least one of o-cresol-formaldehyde epoxy resin, crystalline biphenyl epoxy resin, dicyclohexane pentadiene phenol epoxy resin, biphenyl aralkyl epoxy resin and biphenyl aralkyl epoxy resin.
3. The high performance epoxy molding compound according to claim 1, characterized in that: The curing agent is a phenolic resin, which is at least one selected from linear phenol formaldehyde resin, biphenyl aralkyl type phenolic resin, and X-LOCK type phenolic resin.
4. The high performance epoxy molding compound according to claim 1, characterized in that: The preparation method of the nano modifier is as follows: S1. Dispersing graphene oxide in water, adding nano-silica, stirring and mixing, spray drying, and obtaining wrinkled graphene oxide-coated nano-silica; S2. adding the wrinkled graphene oxide-coated nano-silica to water, adding dopamine hydrochloride and a catalyst, heating and stirring the reaction, centrifuging, washing, and drying to obtain modified wrinkled graphene oxide-coated nano-silica; S3. The prepared modified wrinkled graphene oxide coated nano-silica is reduced with hydrazine hydrate vapor to prepare a nano-modifier.
5. The high performance epoxy molding compound according to claim 4, characterized in that: The mass ratio of graphene oxide and nano-silicon dioxide in step S1 is 3-5:10, and the average particle size of the nano-silicon dioxide is 80-120 nm; the mass ratio of wrinkled graphene oxide-coated nano-silicon dioxide, dopamine hydrochloride and catalyst in step S2 is 10:4-6:0.5-1, the catalyst is a Tris-HCl solution with a pH of 8.5-9.5, the temperature of the heating and stirring reaction is 40-50° C., and the time is 3-5 hours; the reduction time in step S3 is 10-12 hours.
6. The high performance epoxy molding compound according to claim 1, characterized in that: The promoter is a mixture obtained by mixing p-benzoquinone and a triphenylphosphine complex in a molar ratio of 0.5-1.5:
1.
7. The high performance epoxy molding compound according to claim 1, characterized in that: The flame retardant is selected from at least one of N,N'-diglycidyl-2,4,6-tribromoaniline, 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and red phosphorus.
8. The high performance epoxy molding compound according to claim 1, characterized in that: The coupling agent is a silane coupling agent, selected from at least one of KH550, KH602, KH792, and KH560, preferably a mixture of KH550 and KH560, with a mass ratio of 3-5:
4.
9. A method for preparing the high-performance epoxy molding compound according to any one of claims 1 to 8, characterized in that: The following steps are involved: (1) Weigh the raw materials according to the proportion; (2) The raw materials are mixed and added into an open mixer for heating and mixing, cooled and crushed, sieved, and pressed to obtain a high-performance epoxy molding compound.
10. The preparation method according to claim 9, characterized in that: The heating temperature is 80-90° C., the mixing time is 4-7 min, the sieving mesh size is 40-60 mesh, the pressing conditions are 170-180° C., 6-8 MPa, mold closing 50-70 s, and pressure holding 50-70 s.
Citation Information
Patent Citations
A hyperbranched polyphenylene ether epoxy plastic packaging material
CN115558099B